INTERVENSI APOTEKER MENUNJANG PERBAIKAN PERILAKU BEROBAT PENDERITA HIPERTENSI - Ariyani, Herda; Akrom; Alfian, Riza (Jurnal Insan Farmasi Indonesia, 2024)
Based on Riskesdas data (2018), the prevalence of hypertension in South Kalimantan was 10.81% or higher in 2020 compared to the national average of 8.8%. High blood pressure can increase the risk of cardiovascular disease when combined with risk factors like obesity, bad eating habits, smoking, and a sedentary lifestyle. A strategy that incorporates the pharmacist's reminders and motivation through the use of short messaging services (SMS) and modified brief counseling is required to help patients behave better when taking drugs in order to achieve therapeutic success. The purpose of the study is to determine how both interventions affected the drug use of street hypertensive patients at X Hospital Banjarmasin. With a Randomized Pre-test – Post-test Control Group Design, the study project is an experimental quota. The prospective data collection was done on road nursing patients. 34 patients (or 50% of the total) were assigned to the treatment group, and 34 individuals (or 50% of the total) were assigned to the control group, after meeting the inclusion criteria of 68 hypertensive patients. Drug-related behavior questionnaires and interviews were used to gather data. Pharmacists who administered both of these programs found that the treatment group's drug behavior score increased significantly (p<0,05).